Medios de comunicación y calidad informativa - Castelforte Medina, Ylenia Tatiana (2019)
The guideline of this research project has been to determine whether the information quality of the media has an influence on the society where they transmit their content and how the public discriminates what is shown to them on television. Television has expanded in its coverage universes, offering a varied program, from morning news programs, programs for housewives, news, novels or gossip programs, contest programs or realities shows and finally news at the end of the day………